Exploration of the Protective Development Model of Ancient Towns in Metropolitan Suburbs: A Case Study of Xinchang Ancient Town in the Pudong New Area of Shanghai - Gang, Zeng; Siyu, Chen (Journal of landscape research, 2017)
The protection of ancient towns has become a crucial link in the coordinated regional development in China.On the basis of the field investigation,this paper took Xinchang Ancient Town in the Pudong New Area of Shanghai for example to analyze the existing problems in the protection and development of ancient towns,such as narrow economic base,loss of aboriginal culture and vague orientation of urban-rural function,and proposed a protective development model stressing the synergetic development of culture,economy and ecology.That model was designed to enhance local economic competitiveness through the multi-industry linkage,encourage the mass participation,reshape local cultural identity,improve regional ecological environment and optimize the function of Xinchang Ancient Town so that the protection of ancient towns is integrated into the top-level design of the regional comprehensive development.